Creación de una asociación de pequeños productores de brócoli, para el desarrollo local de la parroquia Guaytacama-provincia Cotopaxi. - Granda Duque, Silvana Rocío (2020)
The present work was developed with the objective of knowing the productive system of the community and, through constructive dialogue, to propose agricultural associations for Local Development in Guaytacama. The research was carried out gathering information with interviews with neighborhood presidents, a survey of peasant partners in the sector, scientific reports, articles and web pages. The purpose of this study was to establish the associativity for linking small producers to the broccoli value chain in the Guaytacama parish, implementing a business management that seeks the standardization of its product, seeking support through the state and private companies to consolidate the organization over time and achieve its sustainability.XII For the development of the project five chapters as follows executed, in the first theoretical foundation and methodology to be used is described. In the second chapter, the proposal and development strategy were raised. In the third chapter, the results obtained were presented. The fourth and fifth chapters presented the conclusions and recommendations